Supersaturation-controlled assembly pathway directs hierarchical chirality expression in ionic luminophores - Qiong Wang; Haidi Liu; Ruyuan Zhang; Xinhuan Xu; Youcai Han; Jiannian Yao; Yongli Yan (Proceedings of the National Academy of Sciences, 2026)
The controlled expression of molecular chirality across multiple length scales is a central feature of many natural assemblies, yet remains a significant challenge to achieve in synthetic materials. Here, we show that supersaturation—particularly its temporal evolution—acts as a powerful kinetic parameter for directing chiral expression during antisolvent diffusion. By tuning diffusion conditions, two distinct assembly pathways can emerge from the same ion-paired luminophores. In all cases, nucleation is initiated upon reaching a critical supersaturation threshold, consistent with a common nucleation process. The subsequent growth pathways diverge depending on how supersaturation is sustained over time. When antisolvent diffusion is rapidly completed and the system transitions to an evaporation-dominated regime, gradual reorganization of intermediate assemblies produces macroscopic vortex-like films with pronounced chiral organization, whose large circularly polarized light emission dissymmetry factors (|g CPLE |) originate primarily from structure-induced scattering. In contrast, when supersaturation is continuously maintained through ongoing antisolvent diffusion, higher nucleation density combined with restricted growth leads to square microcrystals that exhibit only weak supramolecular chirality. The two pathways yield distinct chiroptical signatures with opposite CPLE signs and an order-of-magnitude difference in chiroptical response, with vortex films reaching |g CPLE | values up to 0.09. This study establishes a mechanistic link between supersaturation evolution and hierarchical chiral assembly and offers insights for designing macroscopic chiral photonic architectures with relevance to biomimetic and chiroptical applications.